Immunotherapy: Janus Nanobullets Combine Photodynamic Therapy and Magnetic Hyperthermia to Potentiate Synergetic Anti‐Metastatic Immunotherapy (Adv. Sci. 22/2019). Issue 22 (20th November 2019) - Wang, Zheng; Zhang, Fan; Shao, Dan; Chang, Zhimin; Wang, Lei; Hu, Hanze; Zheng, Xiao; Li, Xuezhao; Chen, Fangman; Tu, Zhaoxu; Li, Mingqiang; Sun, Wen; et al.
Abstract : In article number 1901690, Dan Shao, Wen Sun, Wen‐Fei Dong, and co‐workers report the development of Janus magnetic nanoparticles for redox/pH‐triggered photo‐sensitizer release with their matrix‐degradation behavior. Cancer cell membrane cloaking improves combined photodynamic therapy and magnetic hyperthermia in a remarkable anticancer manner, which is harnessed for a synergistic tumor‐specific immune response integrated with an anti‐cytotoxic T lymphocyte‐associated antigen‐4 anti‐body for notable eradication of primary and metastatic breast cancer with low systematic toxicity.